A novel multiplex assay for simultaneously analysing 13 rapidly mutating Y-STRs. (July 2015) - Alghafri, Rashed; Goodwin, Will; Ralf, Arwin; Kayser, Manfred; Hadi, Sibte
Highlights: We present RM-Yplex amplifying 13 rapidly mutating Y-STR markers. A sequenced allelic ladder developed for calling alleles of all loci is described. 8 PT samples with known RM haplotypes showed consistent results using RM-Yplex. Robust allele calls for all markers including multicopy markers up to 62.5 pg DNA. Two male controls 9948 and TaqMan haplotypes are presented for improving calibration. Abstract: A multiplex polymerase chain reaction (PCR) assay (RM-Yplex) was developed which is capable of simultaneously amplifying 13 recently introduced rapidly mutating Y-STR markers (RM Y-STRs). This multiplex assay is expected to aid human identity testing in forensic and other applications to improve differentiating unrelated males and allow separating related males. The 13 RM Y-STR markers included in the multiplex are: DYF387S1, DYF399S1, DYF403S1ab, DYF404S1, DYS449, DYS518, DYS526ab, DYS547, DYS570, DYS576, DYS612, DYS626 and DYS627. This study reflects the proof of concept to analyse all currently known RM Y-STRs simultaneously and describes the optimization of the multiplex assay. The RM-Yplex assay generated complete RM Y-STR profiles down to 62.5 pg of male template DNA, and from male–female DNA mixtures at all ratios tested. We herewith introduce and make available for widespread use in forensic and anthropological studies, an effective and sensitive single multiplex assay for simultaneous genotyping of 13 RM Y-STRs.